2011
DOI: 10.1002/msj.20265
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Fistula in Low and Middle Income Countries

Abstract: Vesicovaginal fistula secondary to obstructed labor continues to be an all-too-common occurrence in underdeveloped nations throughout Africa and Asia. Vesicovaginal fistula remains largely an overlooked problem in developing nations as it affects the most marginalized members of society: young, poor, illiterate women who live in remote areas. The formation of obstetric fistula is a result of complex interactions of social, biologic, and economic influences. The key underlying causes of fistula are the combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 26 publications
1
66
0
1
Order By: Relevance
“…In considering regional issues around obstructed labour, only one article detailed that obstructed labour is common in African women due to the narrow build of their pelvis 20 . It was noted in eighteen articles that many African girls get married at an early age, which increases their risk for obstructed labour, which if not managed leads to prolonged labour [1][2][3][4]11,12,[14][15][19][20][21][22][23][24][25][26][27][28] .…”
Section: Obstructed Labourmentioning
confidence: 99%
See 4 more Smart Citations
“…In considering regional issues around obstructed labour, only one article detailed that obstructed labour is common in African women due to the narrow build of their pelvis 20 . It was noted in eighteen articles that many African girls get married at an early age, which increases their risk for obstructed labour, which if not managed leads to prolonged labour [1][2][3][4]11,12,[14][15][19][20][21][22][23][24][25][26][27][28] .…”
Section: Obstructed Labourmentioning
confidence: 99%
“…One article relied on the WHO's definition of prolonged labour as labour lasting over 24 hours, while noting that in rural settings there are misconceptions as to the ‗normal' length of labour 21 . Six articles detailed that standards set by the WHO are well understood by skilled birth attendants, however, most women in rural settings either deliver by themselves, in the company of family members, or with the aid of traditional birth assistants and are not aware that urgent obstetric care is needed past that point 1,3,11,14,19,21 . One study showed that in some settings, prolonged labour was not considered of enough importance to seek skilled medical care until two to five days had passed 21 .…”
Section: Prolonged Labourmentioning
confidence: 99%
See 3 more Smart Citations